Quantum Spin Exchange Interactions to Accelerate the Redox Kinetics in Li–S Batteries - Du, Yu; Chen, Weijie; Wang, Yu; Yu, Yue; Guo, Kai; Qu, Gan; Zhang, Jianan (Nano-Micro Letters, 2024)
Spin-engineering with electrocatalysts have been exploited to suppress the “shuttle effect” in Li–S batteries. Spin selection, spin-dependent electron mobility and spin potentials in activation barriers can be optimized as quantum spin exchange interactions leading to a significant reduction of the electronic repulsions in the orbitals of catalysts. Herein, we anchor the MgPc molecules on fluorinated carbon nanotubes (MgPc@FCNT), which exhibits the single active Mg sites with axial displacement. According to the density functional theory calculations, the electronic spin polarization in MgPc@FCNT not only increases the adsorption energy toward LiPSs intermediates but also facilitates the tunneling process of electron in Li–S batteries. As a result, the MgPc@FCNT provides an initial capacity of 6.1 mAh cm−2 even when the high sulfur loading is 4.5 mg cm−2, and still maintains 5.1 mAh cm−2 after 100 cycles. This work provides a new perspective to extend the main group single-atom catalysts enabling high-performance Li–S batteries. Highlights: 1 Compared with the traditional single-atom catalysts (SACs), the Mg SACs with axial displacement is accurately fabricated on the functional carbon nanotubes. 2 The electronic spin polarization modulates the spin density of MgPc, facilitating the LiPSs conversion kinetics in Li-S batteries. 3 The MgPc@FCNT achieves ultra-low capacity decay rate under the high sulfur loading.